2021
DOI: 10.1097/ftd.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations and Cardiovascular Effects of Citalopram Enantiomers After Oral Versus Infusion Citalopram Therapy in Dextromethorphan-Mephenytoin-Phenotyped Patients With Major Depression

Abstract: Background: Authors compared plasma concentrations of citalopram (CIT) enantiomers and their metabolites in patients with depression administered either intravenously (IV) or as oral racemic CIT. Then, plasma concentrations were related to the metabolism of probes used for phenotyping patients with depression for CYP2C19 and CYP2D6 activity and cardiovascular functions.Methods: Dextromethorphan-mephenytoin-phenotyped patients with depression were administered racemic CIT (days 1 and 2: 20 mg/d; days 3-10: 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Pharmacokinetic and pharmacogenetic studies in humans demonstrated the involvement of CYP2C19 and CYP2D6 in the N-demethylation of CIT to DCIT (Sindrup et al 1993;Herrlin et al 2003). CYP2C19 preferentially demethylates S-CIT rather than R-CIT (Herrlin et al 2003;Baumann et al 2021). Additional in vitro studies using human liver microsomes described the role of CYP3A4 in addition to CYP2C19 and CYP2D6 in this demethylation step (Kobayashi et al 1997;Rochat et al 1997;Olesen and Linnet 1999;von Moltke et al 1999;von Moltke et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic and pharmacogenetic studies in humans demonstrated the involvement of CYP2C19 and CYP2D6 in the N-demethylation of CIT to DCIT (Sindrup et al 1993;Herrlin et al 2003). CYP2C19 preferentially demethylates S-CIT rather than R-CIT (Herrlin et al 2003;Baumann et al 2021). Additional in vitro studies using human liver microsomes described the role of CYP3A4 in addition to CYP2C19 and CYP2D6 in this demethylation step (Kobayashi et al 1997;Rochat et al 1997;Olesen and Linnet 1999;von Moltke et al 1999;von Moltke et al 2001).…”
Section: Discussionmentioning
confidence: 99%